How can more women with pre-existing type 1 and type 2 diabetes be supported to prepare for pregnancy after a baby loss? A qualitative exploration of lived experiences in the UK - Ruth Bell; Judith Rankin; Eleanor Dyer; Ruth Graham (BMJ Open)
Objectives Explore, understand and analyse how women with pre-existing diabetes can be better supported during the inter-pregnancy interval—the time after a baby loss and before a subsequent pregnancy.Design Qualitative, semi-structured online interviews took place between November 2020 and July 2021. Data were analysed using Reflexive Thematic Analysis.Setting Participants reflected on care received at primary and secondary centres across the UK.Participants Twelve predominantly White, British women with type 1 (n=9) and type 2 (n=3) diabetes with experience of baby loss and subsequent pregnancy were recruited through social media.Results Three interrelated themes: (1) decisions around becoming pregnant after baby loss, (2) the triple burden of baby loss, diabetes and preparing for pregnancy, (3) gaps in the inter-pregnancy interval. Most (n=10) participants wanted to become pregnant again as soon as possible. The short inter-pregnancy interval (median=7 months) highlights a potentially small window of opportunity to support women to grieve and prepare for pregnancy. Providing timely access to care and support in the inter-pregnancy interval without overburdening women might be challenging due to structural issues in services and gaps in referral pathways.Conclusion Women with pre-existing diabetes may experience challenges in accessing appropriate pre-pregnancy care in the inter-pregnancy interval. Our findings suggest that one-size-fits-all approaches are likely to be less effective in meeting diverse needs of this group and that more personalised, targeted support is needed. All healthcare professionals across the different parts of the care provision structure need greater awareness of the issues faced by this group to maximise timely access to the appropriate pre-pregnancy care and support.